Kesetaraan Tingkat Pelayanan Fasilitas Sosial Dalam Perspektif Keadilan Ruang - Setiawan, Rizal; Syahbana, Joesron Alie (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Questions on equality of municipal service facilities, one of which is social facilities, often emerge from people with poor economic status. In addition, the equality application of social facilities service distribution has given birth to service level characteristics based on regional segmentation and economic status. Therefore, the purpose of this study is to assess the form of urban facilities services in the perspective of spatial justice. This study implements empirical examples of junior high school facility services in Surakarta. In addition, to achieve research objectives, the researcher utilizes analysis of service level, descriptive analysis (municipal public transportation network), analysis of service level typology (overlay), analysis of service distribution (autocorrelation moran's I and local indicator of spatial autocorrelation (LISA)), movement network analysis (accessibility) and quantitative analysis of descriptive statistics. Distribution of municipal facility forms concentric pattern. Consumption of services in general follows the social characteristics with random pattern. Service efficiency and effectiveness dominate the areas with concentric pattern. The inhabitants of the service area are generally unable to contribute to the service outcome of supply. Service efficiency and effectiveness are influenced by both social characteristics and criteria.